A De Novo Genome Sequence Assembly of the Arabidopsis thaliana Accession Niederzenz-1 Displays Presence/Absence Variation and Strong Synteny. - Boas Pucker; Daniela Holtgräwe; Thomas Rosleff Sörensen; Ralf Stracke; Prisca Viehöver; Bernd Weisshaar (PLoS ONE, 2016)
Arabidopsis thaliana is the most important model organism for fundamental plant biology. The genome diversity of different accessions of this species has been intensively studied, for example in the 1001 genome project which led to the identification of many small nucleotide polymorphisms (SNPs) and small insertions and deletions (InDels). In addition, presence/absence variation (PAV), copy number variation (CNV) and mobile genetic elements contribute to genomic differences between A. thaliana accessions. To address larger genome rearrangements between the A. thaliana reference accession Columbia-0 (Col-0) and another accession of about average distance to Col-0, we created a de novo next generation sequencing (NGS)-based assembly from the accession Niederzenz-1 (Nd-1). The result was evaluated with respect to assembly strategy and synteny to Col-0. We provide a high quality genome sequence of the A. thaliana accession (Nd-1, LXSY01000000). The assembly displays an N50 of 0.590 Mbp and covers 99% of the Col-0 reference sequence. Scaffolds from the de novo assembly were positioned on the basis of sequence similarity to the reference. Errors in this automatic scaffold anchoring were manually corrected based on analyzing reciprocal best BLAST hits (RBHs) of genes. Comparison of the final Nd-1 assembly to the reference revealed duplications and deletions (PAV). We identified 826 insertions and 746 deletions in Nd-1. Randomly selected candidates of PAV were experimentally validated. Our Nd-1 de novo assembly allowed reliable identification of larger genic and intergenic variants, which was difficult or error-prone by short read mapping approaches alone. While overall sequence similarity as well as synteny is very high, we detected short and larger (affecting more than 100 bp) differences between Col-0 and Nd-1 based on bi-directional comparisons. The de novo assembly provided here and additional assemblies that will certainly be published in the future will allow to describe the pan-genome of A. thaliana.